Strain-Specific Regulation of Striatal Phenotype in Drd2-eGFP BAC Transgenic Mice - Chan, C. Savio (Society for Neuroscience, 2012)
Mice carrying bacterial artificial chromosome (BAC) transgenes have become important tools for neuroscientists, providing a powerful means of dissecting complex neural circuits in the brain. Recently, it was reported that one popular line of these mice—mice possessing a BAC transgene with a D(2) dopamine receptor (Drd2) promoter construct coupled to an enhanced green fluorescent protein (eGFP) reporter—had abnormal striatal gene expression, physiology, and motor behavior. Unlike most of the work using BAC mice, this interesting study relied upon mice backcrossed on the outbred Swiss Webster (SW) strain that were homozygous for the Drd2-eGFP BAC transgene. The experiments reported here were conducted to determine whether mouse strain or zygosity was a factor in the reported abnormalities. As reported, SW mice were very sensitive to transgene expression. However, in more commonly used inbred strains of mice (C57BL/6, FVB/N) that were hemizygous for the transgene, the Drd2-eGFP BAC transgene did not alter striatal gene expression, physiology, or motor behavior. Thus, the use of inbred strains of mice that are hemizygous for the Drd2 BAC transgene provides a reliable tool for studying basal ganglia function.